Ekologi Akal Budi: Memahami Alam sebagai Kesatuan menurut Gregory Bateson - Tumanggor, Bahtiar Jusuf Marulitua (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2020)
While earth has been a living place for human beings, ecology crisis results from the speeding of human civilisation with its sudden jumps on science and technology. This crisis has caused damages in climate changes, global warming, and nature destructions. In spite of the changes in human behaviour, ecological crisis is also caused by epistemological crisis. Mechanistic paradigm leads humans to classify nature based on their own preferences. At the same time, positioning humans over nature brings humans’ hegemony. This article offers Gregory Bateson’s epistemological ideas to understand the unity between human beings and nature. Systemic paradigm can be used to sense nature as oneness of system that leads to the concept of sacrality of the earth. The concept of a sacred earth brings forth a systemic paradigm that shows nature as united with humans. Understanding sacrality as an intrinsic value of nature is a good epistemological start to maintain the ecological sustainability.